NUTRITIVE VALUES OF FERMENTED AND DEFATTED SCRAP FISH MEALS FED TO RED SEA BREAM CHRYSOPHRYS MAJOR - Hossain, M A (Indian Journal of Fisheries, 2011)
Red sea bream Chrysophrys major were reared on highly oxidized scrap fish meal fermented by agroup of micro-organisms and their growth and feed efficiency were compared to those fish reared on nonfermentedand defatted scrap meals and white fish meal. Fermentation by micro-organisms decreasedPOV and TBA but slightly increased VBN content in the scrap meal. The essential amino acids to totalnon-essential amino acids (EAA/NEAA) showed scarcely any difference between non-fermented, defattedor fermented scrap meals. The percentage of w3 HUFA in scrap m;al significantly improved after fermentation.The growth and feed efficiency of fish fed on fermented scrap meal was significantly superior to thoseof the nonfermented scrap meal, and was comparable to those reared on defatted scrap meal or white fishmeal.